Invasive aspergillosis presenting as an intracardiac mass in an immunocompetent host - Bajaj, Nitin (BMJ Case Rep, 2016)
Invasive aspergillosis is a severe fungal infection that primarily affects immunocompromised patients. We report a case of invasive aspergillosis presenting as a febrile respiratory infection with a cardiac mass in an immunocompetent patient. Excision of the intracardiac mass followed by histopathological examination confirmed the diagnosis. The patient was managed with voriconazole, to which he responded well. Rare occurrence of an intracardiac mass with systemic aspergillosis in an immunocompetent host is discussed in this case report.